Islamic Law Review of the Baruga Posambua Tradition in Bahari village South Buton Regency - Irma Purnamayanti; La Jidi; Sufiani Indra Agustini (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
The Baruga Posambua tradition is a tradition of the people of Bahari Village, South Buton Regency, which is held every three years in November, which is a must that must be carried out. The aim of this research is to find out the form of the ritual procession of the Baruga Posambua tradition in the people of Bahari Village, South Buton Regency and a review of Islamic Law. towards the Baruga Posambua tradition in the people of Bahari Village, South Buton Regency. The method in this research is descriptive qualitative using field research. Collecting data or information by referring to observation, documentation and interview guidelines. Furthermore, data analysis techniques are obtained in the form of field notes, photographs, interview transcripts and method of description, depiction or painting in a factual and accurate manner regarding the facts and phenomena being investigated. The results of research from the Islamic Law Review of the Baruga Posambua Tradition show that this tradition does not conflict with Islamic laws because it has the aim of being a form of gratitude to Allah SWT for the good fortune that has been given, as a form of friendship between communities, as a space for soul mates and a form of cultural preservation. in which there are no elements of polytheism.